Caractéristiques sociodémographiques des minorités visibles - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Mauricie-et-du-Centre-du-Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Demographic Profiles of Québec's English-speaking Communities Region of Maurice and la Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Employment Profile of English Speakers in Mauricie - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Mauricie’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Mauricie’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Profil d'emploi des Québécois d'expression anglaise en Mauricie - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de la Mauricie en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de cette région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique de la Mauricie, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC La Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Maskinongé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Shawinigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Trois-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS d'Arthabaska-de l'Érable (0418) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Bécancour - Nicolet-Yamaska (0416) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Trois-Rivières (0415) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Haut-Saint-Maurice (0411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Cap de la Madeleine (04052) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Trois Rivieres (04051) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de L'Energie (0403) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Trois Rivieres (0405) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Haut Saint Maurice (0401) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.